Trophic transfer of cadmium in marine food webs from Western Chilean Patagonia and Antarctica. (December 2018) - Espejo, Winfred; Padilha, Janeide de A.; Kidd, Karen A.; Dorneles, Paulo R.; Barra, Ricardo; Malm, Olaf; Chiang, Gustavo; Celis, José E.
Abstract: In aquatic environments, Cd contamination is a great concern because this non-essential metal presents risks both for wildlife and human health. Data about the concentration and transfer of Cd in Patagonian and Antarctic aquatic food webs are crucial for assessing the impacts of this element in pristine ecosystems. Consequently, the concentration of Cd was measured in thirty-two species collected in the 2014 austral summer from two locations of the Western Patagonia and two locations of the Antarctic Peninsula. The main objective of this work was to assess the relationship between Cd concentration and trophic level determined by δ 15 N. In the studied trophic positions, Cd showed a positive relationship between concentration and trophic level, which suggests biomagnification of this element in macroinvertebrates. However, there was a significant dilution when higher trophic organisms were considered. Highlights: Cadmium was measured in organisms along food chains from remote marine coastal ecosystems. Cadmium concentrations in biota studied here are lower than those measured at lower latitudes. Biomagnification and biodilution of Cd were noted within macroinvertebrates and whole food webs, respectively.